LIM kinase1 regulates mitotic centrosome integrity via its activity on dynein light intermediate chains. Issue 6 (20th June 2018) - Ou, Sirong; Tan, Mei-Hua; Weng, Ting; Li, HoiYeung; Koh, Cheng-Gee
Abstract : Abstract : Abnormal centrosome number and function have been implicated in tumour development. LIM kinase1 (LIMK1), a regulator of actin cytoskeleton dynamics, is found to localize at the mitotic centrosome. However, its role at the centrosome is not fully explored. Here, we report that LIMK1 depletion resulted in multi-polar spindles and defocusing of centrosomes, implicating its involvement in the regulation of mitotic centrosome integrity. LIMK1 could influence centrosome integrity by modulating centrosomal protein localization at the spindle pole. Interestingly, dynein light intermediate chains (LICs) are able to rescue the defects observed in LIMK1-depleted cells. We found that LICs are potential novel interacting partners and substrates of LIMK1 and that LIMK1 phosphorylation regulates cytoplasmic dynein function in centrosomal protein transport, which in turn impacts mitotic spindle pole integrity.